Rethinking neglected tropical diseases: A shift towards more inclusive and equitable terminology. - Marlous L Grijsen; Yonah E Yangaza; Al Kadri; Fidel Strub; Esther E Freeman; Wendemagegn Enbiale (PLOS Global Public Health)
Neglected tropical diseases (NTD) refer to a group of 21 diseases that disproportionally affect impoverished communities in low- and middle-income countries (LMIC) [1]. NTD collectively impact 1.7 billion people, which is about 20% of the world's population [1]. Each year, NTD account for more than 200,000 deaths, with millions left disabled and disfigured due to insufficient access to care and affordable treatment, often leading to social exclusion, stigmatization and discrimination. Although the term NTD has successfully directed funding and resources towards these conditions and encouraged global partnerships and high-level policy initiatives, the term may also have unintended negative consequences. In this paper, we aim to explore the term NTD and stimulate a dialogue that re-evaluates its meaning into more inclusive and equitable language.